2010
DOI: 10.1021/jf9031876
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Vascular Endothelial Function by Procyanidin-Rich Foods and Beverages

Abstract: Flavonoid-rich diets are associated with a lower mortality from cardiovascular disease. This has been linked to improvements in endothelial function. However, the specific flavonoids, or biologically active metabolites, conferring these beneficial effects have yet to be fully defined. In this experimental study of the effect of flavonoids on endothelial function cultured endothelial cells have been used as a bioassay with endothelin-1 (ET-1) synthesis being measured an index of the response. Evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…These results correlate with previous studies in which flavonoids as hesperetin [46] or quercetin decreased ET-1 mRNA levels in HUVECs [25]. Although inhibition of ET-1 expression has been associated with an increment of KLF-2 expression [47], our results fail to show enough evidence to state a relationship between KLF-2 and ET-1. In fact, the most active compounds that inhibit ET-1 expression did not produce higher levels of KLF-2 mRNA.…”
Section: Effects Of Flavonoids On Huvecs Gene Expressionsupporting
confidence: 85%
“…These results correlate with previous studies in which flavonoids as hesperetin [46] or quercetin decreased ET-1 mRNA levels in HUVECs [25]. Although inhibition of ET-1 expression has been associated with an increment of KLF-2 expression [47], our results fail to show enough evidence to state a relationship between KLF-2 and ET-1. In fact, the most active compounds that inhibit ET-1 expression did not produce higher levels of KLF-2 mRNA.…”
Section: Effects Of Flavonoids On Huvecs Gene Expressionsupporting
confidence: 85%
“…Dohadwala et al [19] reported an improvement in vasodilation 2-4 h after a single dose of cranberry juice in an uncontrolled pilot trial, but not following daily consumption (480 mL/day) for 4 week in patients with CAD. Canton et al [52] and Yung et al [53] suggested that procyanidin-rich foods and beverages might decrease ET-1 and increase NO via modulation of their syntheses. However, Mathison et al [14] reported that a single dose of cranberry beverage had no effect on plasma NO in healthy adults and Flammer et al [20] found no change in endothelial function after consumption of a double-strength cranberry juice (460 mL/day) for 4 months in patients with CVD risk factors and endothelial dysfunction.…”
Section: Oxidative Stress and Inflammation Biomarkersmentioning
confidence: 99%
“…Traditionally, polyphenols are considered potent antioxidants. Emerging studies shows that polyphenols may have far more important effects in vivo such as enhancing endothelial function (Caton et al 2010), cellular signalling and anti-inflammatory property (Ramos 2008). Oat hulls have not much uses in food but they contain significant amount of soluble ferulic acid; an avenanthramide antioxidant and also several other phenolic acids.…”
Section: Nutritional Components Of Oatsmentioning
confidence: 99%